A Study of Cervical Cancer Screening At Puskesmas Gianyar I Based On The Social Ecological Model - Wardani, Ni Nyoman Hita Girindra; Wijaya, Made Indra (Jurnal Ilmiah Kesehatan Masyarakat : Media Komunikasi Komunitas Kesehatan Masyarakat, 2025)
Background: Cervical cancer is a leading cause of death among women, and early detection through screening is crucial to prevent its progression. Despite this, participation in screening programs remains low, including in Bali. This study explores factors influencing participation at five levels individual, interpersonal, community, organizational, and policy focusing on the screening program at Puskesmas Gianyar I. Method: The study employed a qualitative approach through in-depth interviews and document analysis. Informants included healthcare workers, the head of the community health center, program coordinators for disease prevention, and patients who had participated in screening. Data were analyzed using thematic analysis to identify key themes aligned with the Social Ecological Model framework. Results: Participation in cervical cancer screening is influenced by the Social Ecological Model. Individual barriers include fear and lack of knowledge, while family and community roles involve support, stigma, and social norms. Organizational challenges include limited facilities and inadequate training, whereas policies require subsidization supported by simplified procedures. Conclusion: This study identifies barriers to cervical cancer screening participation, such as perceptions of being "healthy," stigma, and facility limitations. Promotional strategies are positive but require cultural approaches, enhanced training, and procedural simplifications.